A Comparative Study on the Extraction of Au(III) Using Cyclopentyl Methyl Ether, Dibutyl Carbitol, and Methyl Isobutyl Ketone in Acidic Chloride Media. Issue 5 (19th September 2021) - Oshima, Tatsuya; Koyama, Takao; Otsuki, A. Noriyasu
ABSTRACT: Recently, a commercially available ethereal compound, cyclopentyl methyl ether (CPME) was found to act as an extractant for Au(III) in acidic chloride media. In this study, the extraction behavior of Au(III) using CPME was compared with commercial extractants dibutyl carbitol (DBC) and methyl isobutyl ketone (MIBK). The order of extractability for Au(III) was MIBK > DBC > CPME. The extraction capacity tests indicated that the extraction using the three extractants was unsaturated, and at least 0.30 mol/dm 3 (60 g/dm 3 ) could be loaded onto the three extractants. The extraction selectivity for metal ions using the extractants was similar, but MIBK showed a lower metal selectivity. The extractability of CPME was relatively low compared with DBC and MIBK; however, CPME was advantageous in the stripping and reductive recovery of extracted Au(III). Gold was recovered quantitatively as metallic gold (Au(0)) by reduction using oxalic acid.